High prevalence of fluconazole resistant Candida tropicalis among candiduria samples in China: An ignored matter of concern - Fan, Xin; Tsui, Clement K. M.; Chen, Xi; Wang, Peng; Liu, Zhen-jia; Yang, Chun-xia (Frontiers in Microbiology, 2023)
Introduction The rapid rise of azole resistance in Candida tropicalis causing invasive infections has become a public health concern; however, the prevalence of resistant isolates in urine samples was not well studied, because the clinical significance of candiduria was not unambiguous due to possible host colonization. Methods We performed a 12-year laboratory-based surveillance study of C. tropicalis causing either invasive infection or candiduria and studied their susceptibility profiles to common antifungal drugs. The complete coding domain sequence of the ERG11 gene was amplified in all fluconazole resistant isolates, and aligned with the wild-type sequence to detect nucleotide mutations. Results A total of 519 unique C. tropicalis strains isolates, 69.9% of which were isolated from urine samples and remaining 30.1% were invasive strains. Overall, 16.5% isolates were confirmed to be resistant to fluconazole, of which 91.9% were cross-resistant voriconazole. Of note, at the beginning of surveillance (2010–2011), the fluconazole resistance rates were low in both candiduria and invasive groups (6.8% and 5.9%, respectively). However, the resistant rate in the candiduria group significantly increased to 29.5% since 2012–2013 (p = 0.001) and stayed high since then, whilst the resistance rate in the invasive group only showed a gradually increasing trends till 2021 (p > 0.05). Sequence analysis of ERG11 from fluconazole-resistant strains revealed the prevalence of A395T/W mutations were relatively low (16.7%) in the beginning but reached 87.5–100% after 2014. Moreover, the A395W heterozygous mutation isolates became predominant (>60% of resistant strains) after 2016, and indeed isolates carrying corresponding amino acid substitution (Y132F) was highly resistant to fluconazole with MIC50 exceeded 256 μg/ml. Conclusion Our study revealed high azole resistant rate in candiduria with its increasing trends observed much earlier than stains causing invasive infections. Given antimicrobial resistance as a critical “One Health” issue, the emergence of antifungal resistance in Candida species that are common commensal colonizers in the human body should be concerned.